2004
DOI: 10.1023/b:caco.0000019511.67989.09
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of survival among elderly persons diagnosed with colorectal cancer: does race matter if all are insured? (United States)

Abstract: In this population-based study of elderly Tennesseans covered by both Medicaid and Medicare, there were no significant differences in outcomes, raising the possibility that 'equal coverage*rsquo; leads to more equal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 30 publications
2
54
1
Order By: Relevance
“…As noted earlier, the review of the literature points to a lack of consistency among researchers relative to whether to exclude unstaged cases from the analysis [18,19,20], to group unstaged cases with latestaged cancers [21,22], or even to analyze unstaged cases in a separate stage category [11,14,23,24]. SEER reports survival rates for unstaged cases that are somewhat more favorable than for those with distant stage cancer, but less favorable than for those with regional stage cancer [3,4,5], and a previous study has documented differences in survival patterns among unstaged cases when analysis was performed in age-specific strata [11].…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, the review of the literature points to a lack of consistency among researchers relative to whether to exclude unstaged cases from the analysis [18,19,20], to group unstaged cases with latestaged cancers [21,22], or even to analyze unstaged cases in a separate stage category [11,14,23,24]. SEER reports survival rates for unstaged cases that are somewhat more favorable than for those with distant stage cancer, but less favorable than for those with regional stage cancer [3,4,5], and a previous study has documented differences in survival patterns among unstaged cases when analysis was performed in age-specific strata [11].…”
Section: Discussionmentioning
confidence: 99%
“…38,39 However, in a study that was restricted to patients who were enrolled in both Medicaid and Medicare at the time of their colorectal cancer diagnosis, no racial difference in survival was observed. 40 Dignam et al reported no significant racial difference in cancer-specific survival among patients with colon cancer (HR, 1.08; 95% CI, 0.94-1.25) or rectal cancer (HR, 1.25; 95% CI, 0.94-1.66) who were enrolled in the National Surgical Adjuvant Breast and Bowel Project trials, in which treatment regimens are controlled more rigorously. 35,36 Analyses of patients enrolled in the Phase III Intergroup Trial 0089, which assessed the efficacy of adjuvant chemotherapy (1988)(1989)(1990)(1991)(1992), also indicated that there was no racial difference in survival.…”
Section: Discussionmentioning
confidence: 99%
“…The exact reasons are unknown, but theories of cancer development in the elderly are applicable to colorectal cancer: (1) longer duration of exposure and increased cellular susceptibility to carcinogens, (2) diminished ability to repair damaged DNA, (3) oncogene activation or amplification and tumour suppressor gene loss or malfunction, and (4) diminished immune surveillance mechanisms [3,4].…”
Section: Discussionmentioning
confidence: 99%